Family history in developmental dysplasia of the hip: should we follow-up? - Aydın, Sonay; Fatihoğlu, Erdem (The European Research Journal, 2019)
Objectives: Developmental dysplasia of the hip (DDH) is an important problem. Ultrasonography (US) is a proper method before 6 months of age. For older children, plain radiographs can be useful. Six risk factors are emphasized: breech presentation, female sex, a positive family history, being first-born, left hip affected, and mode of delivery. In some centers, clinicians prefer to perform a control US examination or pelvic radiographs after 6 months of age for the children having a positive family history. We aimed to evaluate the necessity of control US/direct radiography examinations. Methods: A total of 205 children with a positive family history for DDH are included. US examinations are performed according to Graf’s method. We have evaluated direct radiographs by using Hilgenreiner, Perkin, and Shenton lines, acetabular angle. Results: Initial US examinations are performed at a median age of 8.3 weeks. Seventy-four patients (36%) had a repeat ultrasound scan at a median age of 7 months; none of them demonstrated abnormal findings. One hundred and thirty-one patients (63.9%) had control radiographs at a median age of 8.2 months. Shenton line is considered as normal, and the upper femoral epiphysis is located in inferomedial quadrant according to Hilgenreiner and Perkin lines. Conclusions: A positive family history for DDH may be a less important reason for performing control US or radiographic examination. Patients with a normal screening US result and having risk factors can be discharged from follow up safely, so that unnecessary examinations and family anxiety will be reduced.